Gender discrimination and depressive symptoms among child-bearing women: ELSPAC-CZ cohort study - Stepanikova, Irena; Acharya, Sanjeev; Abdalla, Safa; Baker, Elizabeth; Klanova, Jana; Darmstadt, Gary L (EClinicalMedicine, 2020)
BACKGROUND: Depression is approximately two-fold more prevalent among women than men. Social theories suggest that discrimination is a pathway through which gender inequalities affect women's lives, but data are lacking. This cohort study evaluates whether perceived gender discrimination is linked to depressive symptoms among child-bearing women. METHODS: Data were obtained from 4,688 participants enrolled in pregnancy in 1991-92 in the European Longitudinal Cohort Study of Pregnancy and Childhood, Czech Republic. Perceived gender discrimination was assessed in mid-pregnancy, year seven, and year eleven. Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale at eight time-points between mid-pregnancy and year eleven post-delivery. Linear mixed error-component models of depressive symptoms were estimated. FINDINGS: Perceived gender discrimination, reported by 10.7% of women, was related to higher depressive symptoms, both in the unadjusted analysis (b = 0.15 [95% confidence interval (CI): 0.12, 0.19], p < 0.001) and in the fully adjusted model (b = 0.12 [95% CI: 0.09, 0.16], p < 0.001). Covariates linked to higher depressive symptoms included financial hardship (b = 0.12 [95% CI: 0.10, 0.14], p < 0.001), childhood emotional/physical neglect (b = 0.18 [95% CI: 0.14, 0.22], p < 0.001), and childhood sexual abuse (b = 0.04 [95% CI: 0.03, 0.06], p < 0.001); an inverse relationship was evident for social support (-0.05 [95% CI: -0.07, -0.04], p < 0.001) and having a partner who performs female-stereotypical household tasks (b=-0.03 [95% CI: -0.05, -0.01], p = 0.001). INTERPRETATION: The findings provide the first evidence that perceived gender discrimination is associated with depressive symptoms among child-bearing women. Social intervention programs aimed at reducing gender discrimination can potentially contribute to better mental health of women. FUNDING: Bill and Melinda Gates Foundation.
Keywords: Depressive symptoms; Gender; Mental health